Diplodia corticola and Phytophthora cinnamomi : the main pathogens involved in holm oak decline on Caprera Island (Italy) - Linaldeddu, B. T.; Scanu, B.; Maddau, L.; Franceschini, A. (Forest Pathology, 2014)
Since 2008, severe and widespread tree decline and mortality has been observed at the main growing Quercus ilex L. (holm oak) forest on Caprera Island, Italy. To clarify the symptomatology and aetiology of this phenomenon, field surveys and isolations from symptomatic trees were carried out in summer 2010. Affected trees exhibited crown thinning, branch dieback, sunken cankers, epicormic shoots, exudates on branches and trunk, root losses and sudden death symptoms. Four fungal species belonging to Botryosphaeriaceae family, namely Botryosphaeria dothidea, Diplodia corticola, D. seriata and Neofusicoccum parvum, were isolated from cankers on trunk and branches, whereas three species of Phytophthora, namely P. cinnamomi, P. cryptogea and P. gonapodyides, were isolated from fine roots and rhizosphere soil samples. Isolates were identified using both morphological analysis and DNA-based techniques. Pathogenicity trials on holm oak seedlings showed that all the isolated species are pathogenic. D. corticola proved to be the most aggressive species. Our results provide the first evidence for a combined involvement of D. corticola and P. cinnamomi in the aetiology of holm oak decline in Italy and suggest that these pathogens are not only important contributing factors in the onset of long-term tree decline, but also may cause the rapid devastation of extensive oak ecosystems.
Key words by Adriana SilvaKey words by Adriana SilvaThe following values have no corresponding Zotero field: label: APS;Quercus ilex L.;fungus;mortality;pathogens;tree decline
Keywords: APS; Fungus; mortality; pathogens; Quercus ilex L.; tree decline

Environmental risk assessment of carbosulfan on target and non-target beetles when used as white grub larvicide in the cork oak forest of Mamora (Morocco) - Fegrouche, R; Kadiri, N; Ghailoule, D; Kadiri, Z Atay; Lumaret, J -P. (INTERNATIONAL JOURNAL OF PEST MANAGEMENT, 2014)
The protection of new cork oak plantations against the larvae of the beetle Sphodroxia maroccana (Melolonthidae), which destroy the roots of newly planted trees, was provided for many years in the forest of Mamora in Morocco by the use of carbosulfan, usually formulated as dry granules for direct incorporation into the soil at planting. Ecotoxicological tests were conducted in the laboratory on S. maroccana and on two non-target beetle species, namely Pachychila obtusecostata and Pimelia platynota (Tenebrionidae), to measure the acute effects of carbosulfan and evaluate the potential risk associated with inappropriate practices. The mortality was measured at both 4 d and 7 d after ingestion of a known quantity of carbosulfan. The recommended dose by the manufacturer was exceeded by at least four-fold in the Mamora Forest, with obvious environmental risks. Risks were identified for wildlife when the pesticide is misused and spread on the soil around the plants.
Keywords: carbosulfan; Cork oak; environmental risk; Melolonthidae; Morocco; mortality; Pachychila obtusecostata; Pimelia platynota; Sphodroxia maroccana; Tenebrionidae

Decline of Mediterranean oak trees and its association with Phytophthora cinnamomi: a review - de Sampaio e Paiva Camilo-Alves, Constança; Clara, MariaIvoneEsteves; Almeida Ribeiro, NunoManuelCabral (European Journal of Forest Research, 2013)
Mortality events in cork and holm oaks have occurred in the Mediterranean basin since the beginning of the XX century, but severity of decline increased during the 1980s. By that time, the exotic soil borne pathogen Phytophthora cinnamomi was often recovered from declining stands and since then it has been considered the main factor associated with decline. This work analyses data concerning P. cinnamomi surveys in cork and holm oaks trees, pathogenicity tests carried out in controlled experiments, studies about the influence of site characteristics in tree decline and approaches to control the disease. Results of field surveys showed that the pathogen is widespread and pathogenicity tests suggested that host susceptibility to the pathogen is moderate when seedlings are in appropriate watering conditions, particularly cork oaks. Occurrence of decline is also associated with soil characteristics that interfere with root expansion and water retention. We assessed the relative importance of each factor involved in decline and revised the role of P. cinnamomi in cork and holm oak decline.
APSAPSThe following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: mortality; pathogenes; Quercus ilex L.; Quercus suber L.; tree decline

Multivariate effect gradients driving forest demographic responses in the Iberian Peninsula - Coll, Marta; Penuelas, Josep; Ninyerola, Miquel; Pons, Xavier; Carnicer, Jofre (Forest Ecology and Management, 2013)
A precise knowledge of forest demographic gradients in the Mediterranean area is essential to assess future impacts of climate change and extreme drought events. Here we studied the geographical patterns of forest demography variables (tree recruitment, growth and mortality) of the main species in Spain and assessed their multiple ecological drivers (climate, topography, soil, forest stand attributes and tree-spe- cific traits) as well as the geographical variability of their effects and interactions. Quantile modeling analyses allowed a synthetic description of the gradients of multiple covariates influencing forest demog- raphy in this area. These multivariate effect gradients showed significantly stronger interactions at the extremes of the rainfall gradient. Remarkably, in all demographic variables, qualitatively different levels of effects and interactions were observed across tree-size classes. In addition, significant differences in demographic responses and effect gradients were also evident between the dominant genus Quercus and Pinus. Quercus species presented significantly higher percentage of plots colonized by new recruits, whereas in Pinus recruitment limitation was significantly higher. Contrasting positive and negative growth responses to temperature were also observed in Quercus and Pinus, respectively. Overall, our results synthesize forest demographic responses across climatic gradients in Spain, and unveil the inter- actions between driving factors operating in the drier and wetter edges.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Forest demography; Growth; Macroecology; mortality; Quantile modeling; Recruitment

Post-fire response variability in Mediterranean Basin tree species in Portugal - Catry, Filipe X.; Pausas, Juli G.; Moreira, Francisco; Fernandes, Paulo M.; Rego, Francisco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2013)
Fire is the most important natural disturbance driving vegetation dynamics in the Mediterranean Basin. However, studies relating fire-induced tree responses to both fire severity and plant traits are still scarce in this region. We aimed to investigate such relationships further and to develop simple models that could help improve forest management in these fire-prone ecosystems. We compiled data from 16 fire sites in different regions and used models to relate post-fire responses of 4155 trees from 14 species with fire severity indicators and tree characteristics. The influence of several spatiotemporal factors at the site level was also considered. Results showed that pine mortality was usually high and mainly determined by fire severity, whereas plant traits played a minor role. In contrast, mortality of broadleaved trees was usually low, even for high-severity fire, but most trees were top-killed. Stem mortality increased with fire severity and decreased with bark thickness and tree size. The models for predicting individual mortality of pines and stem mortality of broadleaves showed very good performance, including when validated against independent datasets. Our results suggest that it is possible to accurately predict the most common post-fire responses of Mediterranean species based on simple fire and tree characteristics.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: broadleaves; experimental fire; Modelling; mortality; pines; top-kill; Wildfire

Cork Oak Vulnerability to Fire: The Role of Bark Harvesting, Tree Characteristics and Abiotic Factors - Catry, Filipe X; Moreira, Francisco; Pausas, Juli G; Fernandes, Paulo M; Rego, Francisco; Cardillo, Enrique; Curt, Thomas (PLoS ONE, 2012)
Forest ecosystems where periodical tree bark harvesting is a major economic activity may be particularly vulnerable to disturbances such as fire, since debarking usually reduces tree vigour and protection against external agents. In this paper we asked how cork oak Quercus suber trees respond after wildfires and, in particular, how bark harvesting affects post-fire tree survival and resprouting. We gathered data from 22 wildfires (4585 trees) that occurred in three southern European countries (Portugal, Spain and France), covering a wide range of conditions characteristic of Q. suber ecosystems. Post-fire tree responses (tree mortality, stem mortality and crown resprouting) were examined in relation to management and ecological factors using generalized linear mixed-effects models. Results showed that bark thickness and bark harvesting are major factors affecting resistance of Q. suber to fire. Fire vulnerability was higher for trees with thin bark (young or recently debarked individuals) and decreased with increasing bark thickness until cork was 3–4 cm thick. This bark thickness corresponds to the moment when exploited trees are debarked again, meaning that exploited trees are vulnerable to fire during a longer period. Exploited trees were also more likely to be top-killed than unexploited trees, even for the same bark thickness. Additionally, vulnerability to fire increased with burn severity and with tree diameter, and was higher in trees burned in early summer or located in drier south-facing aspects. We provided tree response models useful to help estimating the impact of fire and to support management decisions. The results suggested that an appropriate management of surface fuels and changes in the bark harvesting regime (e.g. debarking coexisting trees in different years or increasing the harvesting cycle) would decrease vulnerability to fire and contribute to the conservation of cork oak ecosystems.
Keywords: bark tickness; cork harvesting; Cork oak; fire; fire vulnerability; management (voyant); mortality; post-fire response

Drought-Induced Multifactor Decline of Scots Pine in the Pyrenees and Potential Vegetation Change by the Expansion of Co-occurring Oak Species - Galiano, L.; Martínez-Vilalta, J.; Lloret, F. (Ecosystems, 2010)
Episodes of drought-induced tree dieback have been recently observed in many forest areas of the world, particularly at the dry edge of species distributions. Under climate change, those effects could signal potential vegetation shifts occurring over large geographical areas, with major impacts on ecosystem form and function. In this article, we studied the effect of a single drought episode, which occurred in summer 2005, on a Scots pine population in central Pyrenees (NE Spain). Our main objective was to study the environmental correlates of forest decline and vegetation change at the plot level. General and generalized linear models were used to study the relationship between canopy defoliation, mortality and recruitment, and plot characteristics. A droughtdriven multifactor dieback was observed in the study forest. Defoliation and mortality were associated with the local level of drought stress estimated at each plot. In addition, stand structure, soil properties, and mistletoe infection were also associated with the observed pattern of defoliation, presumably acting as long-term predisposing factors. Recruitment of Scots pine was low in all plots. In contrast, we observed abundant recruitment of other tree species, mostlyQuercus ilexand Q. humilis, particularly in plots where Scots pine showed high defoliation and mortality. These results suggest that an altitudinal upwards migration of Quercusspecies, mediated by the dieback of the currently dominant species, may take place in the studied slopes. Many rear-edge populations of Scots pine sheltered in the mountain environments of the Iberian Peninsula could be at risk under future climate scenarios.
Keywords: canopy defoliation; Drought; mistletoe; mortality; pinus sylvestris l; Recruitment; scots pine; scots pine (Pinus sylvestris L.); soil properties; Stand Structure; summer; summer water availability; Water availability

A conceptual model of sprouting responses in relation to fire damage: an example with cork oak (Quercus suber L.) trees in Southern Portugal - Moreira, Francisco; Catry, Filipe; Duarte, Inês; Acácio, Vanda; Silva, Joaquim Sande (Plant Ecology, 2008)
The sprouting response types of 1,151 cork oak (Quercus suber) trees one and half years after a wildﬁre in southern Portugal were characterised. It was hypothesised that different response types should occur according to the following conceptual model: an increased level of damage (ﬁre severity) on a sprouting tree that suffered a crown ﬁre was expected to be reﬂected in a sequence of four alternative events, namely (a) resprouting exclusively from crown, (b) simultaneous resprouting from crown and base, (c) resprouting exclusively from base and (d) plant death. To assess whether the level of expected damage was inﬂuenced by the level of protection from disturbance, we explored the relationships between response types and tree size, bark thickness and cork stripping, using an informationtheoretic approach. The more common response type was crown resprouting (68.8% of the trees), followed by plant death (15.8%), simultaneous resprouting from crown and base (10.1%) and basal resprouting (5.3%). In agreement with the conceptual model, trees which probably suffered a higher level of damage by ﬁre (larger trees with thinner bark; exploited for cork) died or resprouted exclusively from base. On the other hand, trees that were well protected (smaller trees with thicker bark not exploited for cork) were able to rebuild their canopy through crown resprouting. Simultaneous resprouting from the crown and base was determined mainly by tree size, and it was more common in smaller trees.
Keywords: apical dominance; Mediterranean; model; mortality; resource allocation; resprouting; severity

Seedling performance in sewage sludge-amended degraded Mediterranean woodlands - FUENTES, D.; VALDECANTOS, A.; CORTINA, J.; Vallejo, V.R. R (Ecological Engineering, 2007)
Biosolids have been widely used for land reclamation, but information on their use in restoration, i.e., on less degraded areas, is scarce. Biosolids may be used to restore forest ecosystems by fostering tree establishment in degraded shrublands. Detailed knowledge on the effects of biosolid application is needed to optimize such practice. We evaluated the effect of different rates (0, 7.5 and 14.5 kg dry weight per plant) and types of biosolid application on the performance of Pinus halepensis and Quercus ilex seedlings, and operational costs. Biosolids increased seedling mortality in both species, particularly when seedlings were planted in direct contact with them. Mortality mostly occurred during the ﬁrst year, and was probably favored by soil shrinking and salinity. Foliar and needle nitrogen concentration increased with biosolid rate in the short term, but biosolids affected negatively (P. halepensis), or had no effect (Q. ilex) on phosphorus and potassium concentration. Biosolids had a positive effect on P. halepensis growth, and a negative effect on Q. ilex growth at the highest rate when seedlings were in contact with biosolids. Cost of this type of biosolid application approximately doubled plantation cost, but were similar or cheaper that landﬁll disposal of biosolids. The lowest application rate showed the best balance between seedling response and costs for P. halepensis, whereas biosolid use cannot be recommended for Q. ilex.
Keywords: mortality; Pinus halepensis; Quercus ilex; Restoration; Salinity; seedling growth; Sewage sludge

Seedling performance in sewage sludge-amended degraded Mediterranean woodlands - FUENTES, D.; Valdecantos, a; CORTINA, J.; Vallejo, V. R. R. (Ecological Engineering, 2007)
Biosolids have been widely used for land reclamation, but information on their use in restoration, i.e., on less degraded areas, is scarce. Biosolids may be used to restore forest ecosystems by fostering tree establishment in degraded shrublands. Detailed knowledge on the effects of biosolid application is needed to optimize such practice. We evaluated the effect of different rates (0, 7.5 and 14.5 kg dry weight per plant) and types of biosolid application on the performance of Pinus halepensis and Quercus ilex seedlings, and operational costs. Biosolids increased seedling mortality in both species, particularly when seedlings were planted in direct contact with them. Mortality mostly occurred during the ﬁrst year, and was probably favored by soil shrinking and salinity. Foliar and needle nitrogen concentration increased with biosolid rate in the short term, but biosolids affected negatively (P. halepensis), or had no effect (Q. ilex) on phosphorus and potassium concentration. Biosolids had a positive effect on P. halepensis growth, and a negative effect on Q. ilex growth at the highest rate when seedlings were in contact with biosolids. Cost of this type of biosolid application approximately doubled plantation cost, but were similar or cheaper that landﬁll disposal of biosolids. The lowest application rate showed the best balance between seedling response and costs for P. halepensis, whereas biosolid use cannot be recommended for Q. ilex.
Keywords: mortality; Pinus halepensis; Quercus ilex; Restoration; Salinity; seedling growth; Sewage sludge

Effects of fire on tree survival and regeneration in a Mediterranean ecosystem - Catry, Filipe Xavier; Rego, Francisco Castro; Bugalho, Miguel Nuno; Lopes, Tito; Silva, Joaquim Sande; Moreira, Francisco (Forest Ecology and Management, 2006)
Portugal is the only European Mediterranean country where the annual average burnt area has increased in the last two decades. Although forest ﬁres at national level annually represent very important losses, few studies evaluated the mortality and the capacity of auto-regeneration of the different tree species in burnt areas. After a wildﬁre that occurred in September 2003, we started a research project in a public protected area in central west Portugal. The main goal of this study, still ongoing, is to evaluate the post-ﬁre regeneration capacity of different tree species occurring in the country. We expect to quantify the survival/mortality rates of selected tree species in relation to variables such as ﬁre severity, tree height and diameter, and evaluate species regeneration strategies as well as their growth rates after ﬁre disturbance. In this study 667 trees from 11 species were selected for monitoring, namely: Castanea sativa, Crataegus monogyna, Eucalyptus globulus, Fraxinus angustifolia, Olea europaea var. sylvestris, Pinus pinaster, Pinus pinea, Pistacia lentiscus, Quercus coccifera, Quercus faginea and Quercus suber. Results obtained two springs after ﬁre, show that almost all broadleaved trees (9 species) survived to the ﬁre. Contrarily, the majority of coniferous trees died after the ﬁre. Despite the very low mortality observed in broadleaved trees, most of them did not regenerate from the crown, but only from the base, trunk or roots, which means that the recovering process will be much slower. Exceptions to this were cork oak and eucalyptus. Within native species, Quercus suber is by far the most resilient to ﬁre. For most part of the monitored tree species, which resprouted from the base of the trunk, Eucalyptus globulus was the one that recovered faster, followed by Fraxinus angustifolia and Quercus faginea.
Keywords: mortality; natural regeneration; post-ﬁre recovery; Tree species

Effects of fire on tree survival and regeneration in a Mediterranean ecosystem - Catry, Filipe Xavier; Rego, Francisco Castro; Bugalho, Miguel Nuno; Lopes, Tito; Silva, Joaquim Sande; Moreira, Francisco (Forest Ecology and Management, 2006)
Portugal is the only European Mediterranean country where the annual average burnt area has increased in the last two decades. Although forest ﬁres at national level annually represent very important losses, few studies evaluated the mortality and the capacity of auto-regeneration of the different tree species in burnt areas. After a wildﬁre that occurred in September 2003, we started a research project in a public protected area in central west Portugal. The main goal of this study, still ongoing, is to evaluate the post-ﬁre regeneration capacity of different tree species occurring in the country. We expect to quantify the survival/mortality rates of selected tree species in relation to variables such as ﬁre severity, tree height and diameter, and evaluate species regeneration strategies as well as their growth rates after ﬁre disturbance. In this study 667 trees from 11 species were selected for monitoring, namely: Castanea sativa, Crataegus monogyna, Eucalyptus globulus, Fraxinus angustifolia, Olea europaea var. sylvestris, Pinus pinaster, Pinus pinea, Pistacia lentiscus, Quercus coccifera, Quercus faginea and Quercus suber. Results obtained two springs after ﬁre, show that almost all broadleaved trees (9 species) survived to the ﬁre. Contrarily, the majority of coniferous trees died after the ﬁre. Despite the very low mortality observed in broadleaved trees, most of them did not regenerate from the crown, but only from the base, trunk or roots, which means that the recovering process will be much slower. Exceptions to this were cork oak and eucalyptus. Within native species, Quercus suber is by far the most resilient to ﬁre. For most part of the monitored tree species, which resprouted from the base of the trunk, Eucalyptus globulus was the one that recovered faster, followed by Fraxinus angustifolia and Quercus faginea.
Keywords: mortality; natural regeneration; post-ﬁre recovery; Tree species

Topography and forest composition affecting the variability in fire severity and post-fire regeneration occurring after a large fire in the Mediterranean basin - Broncano, M. J.; Retana, J. (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2004)
This study relates the spatial variability in tree regeneration generated by fire with topography and pre-fire vegetation composition, and analyses how the pattern of fire severities determines post-fire regeneration of the dominant tree species (Pinus halepensis and Quercus ilex) in a large fire that occurred in north-eastern Spain in summer 1994. At the fire level, the proportion of the different fire severities in the burned area was characteristic of large fires that burn with high severity. At the level of plot, the variability of fire severity in the study site depended on two topographic characteristics: elevation and aspect. Plots burned with high fire severity were distributed at higher altitude than less severely burned plots, which were mainly distributed in south- and east-facing slopes. Fire severity also increased with Q. ilex density in the stand. The mosaic of fire severities determined both plant mortality and seedling regeneration. Mortality of stems caused by fire was very high in both species, but many Q. ilex individuals resprouted after fire. Seedling regeneration of P. halepensis showed large differences among plots in the burned area, reflecting large spatial variability due to the elevation gradient, the variation in density of adult pine trees, and the spatial variability created by fire.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: mortality; post-fire regeneration; resprouting

Topography and forest composition affecting the variability in fire severity and post-fire regeneration occurring after a large fire in the Mediterranean basin - Broncano, M J; RETANA, J (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2004)
This study relates the spatial variability in tree regeneration generated by fire with topography and pre-fire vegetation composition, and analyses how the pattern of fire severities determines post-fire regeneration of the dominant tree species (Pinus halepensis and Quercus ilex) in a large fire that occurred in north-eastern Spain in summer 1994. At the fire level, the proportion of the different fire severities in the burned area was characteristic of large fires that burn with high severity. At the level of plot, the variability of fire severity in the study site depended on two topographic characteristics: elevation and aspect. Plots burned with high fire severity were distributed at higher altitude than less severely burned plots, which were mainly distributed in south- and east-facing slopes. Fire severity also increased with Q. ilex density in the stand. The mosaic of fire severities determined both plant mortality and seedling regeneration. Mortality of stems caused by fire was very high in both species, but many Q. ilex individuals resprouted after fire. Seedling regeneration of P. halepensis showed large differences among plots in the burned area, reflecting large spatial variability due to the elevation gradient, the variation in density of adult pine trees, and the spatial variability created by fire.
Keywords: mortality; post-fire regeneration; resprouting

Thinning effects on carbon allocation to fine roots in a Quercus ilex forest - López, B. C.; Sabate, S.; Gracia, C. A. (Tree Physiology, 2003)
The dynamics of the fine root system are relevant to calculations of the carbon balance of the ecosystem, and there is also a need to quantify changes in this component caused by disturbances. Mediterranean forest systems have historically been coppiced to obtain charcoal. As a result of the resprouting capacity of holm oaks (Quercus ilex L.), these forests present more than 50% of their biomass below ground (stump + roots > 1 cm in diameter), but the effects of thinning on the fine root system are unknown. Fine root biomass, production, mortality and longevity were studied in a control and a thinned Mediterranean holm oak forest by minirhizotron methodology. Observations of fine roots started 2 years after thinning and continued for almost 3 years. Extraction of 80% of the former basal area of the forest greatly affected carbon allocation patterns. Biomass increased by more than 100%, production increased by 76%, mortality increased by 32% and longevity decreased by around 2 weeks. The greatest differences between treatments were associated with differences in growth during autumn months in the top 40 cm of soil, particularly between 10 and 20 cm depth.
10.1093/treephys/23.17.121710.1093/treephys/23.17.1217
Keywords: biomass; longevity; mortality; production

Thinning effects on carbon allocation to fine roots in a Quercus ilex forest - López, B C; Sabate, S; Gracia, C A (Tree Physiology, 2003)
The dynamics of the fine root system are relevant to calculations of the carbon balance of the ecosystem, and there is also a need to quantify changes in this component caused by disturbances. Mediterranean forest systems have historically been coppiced to obtain charcoal. As a result of the resprouting capacity of holm oaks (Quercus ilex L.), these forests present more than 50% of their biomass below ground (stump + roots > 1 cm in diameter), but the effects of thinning on the fine root system are unknown. Fine root biomass, production, mortality and longevity were studied in a control and a thinned Mediterranean holm oak forest by minirhizotron methodology. Observations of fine roots started 2 years after thinning and continued for almost 3 years. Extraction of 80% of the former basal area of the forest greatly affected carbon allocation patterns. Biomass increased by more than 100%, production increased by 76%, mortality increased by 32% and longevity decreased by around 2 weeks. The greatest differences between treatments were associated with differences in growth during autumn months in the top 40 cm of soil, particularly between 10 and 20 cm depth.
10.1093/treephys/23.17.1217
Keywords: biomass; longevity; mortality; production

Chlorophyll fluorescence, stress and survival in populations of Mediterranean grassland species - Figueroa, M E (Journal of Vegetation Science, 1997)
Photosynthetic stress in response to a natural episode of frost and seasonal drought was assessed in a ‘dehesa’ grassland of SW Spain with a portable fluorimeter. Chlorophyll fluorescence characteristics of dark-adapted leaves of 11 abundant species of Mediterranean grassland were measured over the course of a growing season from November 1992 to July 1993. Concomitant changes in population size were estimated from censuses of permanent quadrats. There was a general decline in the photochemical efficiency (F v /Fm ) during the growing season and this was particularly evident late in the growing season (spring and early summer) when ambient temperatures were increasing rapidly and rainfall was low; it coincided with the period of most intense mortality for most species. A frost in early March (– 5 °C), when photosynthetically active radiation was relatively high, resulted in a small decrease in F v /Fm that was consistent across many species. The mechanisms of protection in species of Mediterranean grassland appear to be sufficiently effective to avoid damage to PSII for most of the year. For most species there was little evidence of photosystem II damage, as initial fluorescence (F 0 ) usually did not increase. Many of the effects observed were due to a reduction in Fm and thus were consistent with non-photochemical quenching. This could be adaptive in protecting PSII from damage in species that show little evidence of stress. The sharp increase in stress toward the end of the life cycle coincided with the fall in net population size.
Keywords: Drought; Fv/Fm; mortality; Photo-inhibition; photochemical efficiency; Photosystem II

Chlorophyll fluorescence, stress and survival in populations of Mediterranean grassland species - Figueroa, M. E. (Journal of Vegetation Science, 1997)
Photosynthetic stress in response to a natural episode of frost and seasonal drought was assessed in a ‘dehesa’ grassland of SW Spain with a portable fluorimeter. Chlorophyll fluorescence characteristics of dark-adapted leaves of 11 abundant species of Mediterranean grassland were measured over the course of a growing season from November 1992 to July 1993. Concomitant changes in population size were estimated from censuses of permanent quadrats. There was a general decline in the photochemical efficiency (F v /Fm ) during the growing season and this was particularly evident late in the growing season (spring and early summer) when ambient temperatures were increasing rapidly and rainfall was low; it coincided with the period of most intense mortality for most species. A frost in early March (– 5 °C), when photosynthetically active radiation was relatively high, resulted in a small decrease in F v /Fm that was consistent across many species. The mechanisms of protection in species of Mediterranean grassland appear to be sufficiently effective to avoid damage to PSII for most of the year. For most species there was little evidence of photosystem II damage, as initial fluorescence (F 0 ) usually did not increase. Many of the effects observed were due to a reduction in Fm and thus were consistent with non-photochemical quenching. This could be adaptive in protecting PSII from damage in species that show little evidence of stress. The sharp increase in stress toward the end of the life cycle coincided with the fall in net population size.
Keywords: Drought; Fv/Fm; mortality; Photo-inhibition; photochemical efficiency; Photosystem II